CSR DISCLOSURE DAN FAKTOR LAIN YANG MEMPENGARUHI MANAJEMEN LABA - Melvany, Mellvy; Suryanto, Suryanto (E-Jurnal Akuntansi TSM, 2025)
The purpose of this study was to obtain empirical evidence of the effect of accounting conservatism, corporate social responsibility disclosure, tax avoidance, leverage, company age, and profitability on earnings management.The population that is used in this research are manufacturing companies listed in the Indonesia Stock Exchange from 2021 to 2023 and apply purposive sampling as the sampling method. With this method, it is obtained that 70 manufacturing companies fit with the sampling criteria and selected as the sample with the total of 208 data. Data analysis in this study used multiple regression method in hypothesis testing.The results of this study indicate that accounting conservatism, corporate social responsibility disclosure and profitability has a negative effect on earnings management. This means that the higher the accounting conservatism, corporate social responsibility disclosure and profitability, the lower the earnings management. Tax avoidance has a positive effect on earnings management. This means that the higher the tax avoidance, the higher the earnings management. Meanwhile, company age and leverage has no effect on earnings management.